Lika-Liku Perkembangan Filsafat Ilmu Syariah, dan Apakah Bermanfaat bagi Dunia Perbankan? - Richard Andrew (ITB AAS INDONESIA Surakarta, 2023)
Islamic banking philosophy continues to experience rapid development. In Indonesia, the concept of Sharia continues to grow and widely used in every aspects, especially in the banking sector. Since declare of the Sharia banking-law in 2008, Islamic banking has experienced significant development. Dinamica of fatwa MUI, as institution authorized to issue 140 fatwas on Sharia financial and banking principles. OJK successfully prepares Banking Development Roadmap Sharia 2020-2025 to encourage the development of the Islamic. The performance of the financial industry is better than conventional banks in the midst of the Covid-19 pandemic. The public literacy index for Islamic banking is only 8.93 percent compared conventional banks of 37.72 percent.The government is committed to encouraging the birth of a halal Industrial Park Center supported by the development of the largest sharia-based financial system in the world. The purpose of this study to determine how beneficial the development of Islamic philosophy in the banking. The research method follows the various dynamics of the development of relevant Sharia studied based on the philosophy of Islamic law and the politics of Islamic law. The results showed that the philosophy of Islamic banking has a significant impact on the overall economy of Bank Syariah.